This is kind of a neat problem about roots.
\(\displaystyle h\ and\ \dfrac{1}{h}\ are\ roots\ of\ ax^2 + bx + c \implies \ c = a,\ and\ b = \dfrac{-a(h^2 + 1)}{h}.\)
Proof
\(\displaystyle a(x - h)\left(x - \dfrac{1}{h}\right) = 0 \implies a\left(x^2 - hx - \dfrac{x}{h} + 1\right) = 0 \implies\)
\(\displaystyle a\left(x^2 - \dfrac{h^2x - x}{h} + 1\right) = 0 \implies ax^2 + \left(\dfrac{-a(h^2 + 1)}{h}\right)x + a = 0 \implies\)
\(\displaystyle b = \dfrac{-a(h^2 + 1)}{h}\ and\ c = a.\)
\(\displaystyle \ c = a,\ and\ b = \dfrac{-a(h^2 + 1)}{h} \implies h\ and\ \dfrac{1}{h}\ are\ roots\ of\ ax^2 + bx + c.\)
Proof
\(\displaystyle ax^2 + bx + c = 0 \implies ax^2 + \left(\dfrac{-a(h^2 + 1)}{h}\right)x + a = 0 \implies x^2 + \left(\dfrac{-(h^2 + 1)}{h}\right)x + 1 = 0 \implies\)
\(\displaystyle x = \dfrac{\dfrac{h^2 + 1}{h} \pm \sqrt{\dfrac{h^4 + 2h^2 + 1}{h^2} - (4 * 1 * 1)}}{2 * 1} = \dfrac{\dfrac{h^2 + 1}{h} \pm \sqrt{\dfrac{h^4 + 2h^2 + 1}{h^2} - \dfrac{4h^2}{h^2}}}{2} =\)
\(\displaystyle \dfrac{\dfrac{h^2 + 1}{h} \pm \sqrt{\dfrac{h^4 - 2h^2 + 1}{h^2}}}{2} = \dfrac{\dfrac{h^2 + 1}{h} \pm \sqrt{\left(\dfrac{h^2 - 1}{h}\right)^2}}{2} \implies\)
\(\displaystyle x = \dfrac{\dfrac{h^2 + 1}{h} + \dfrac{h^2 - 1}{h}}{2} = \dfrac{\dfrac{2h^2}{h}}{2} = h\ OR\)
\(\displaystyle x = \dfrac{\dfrac{h^2 + 1}{h} - \dfrac{h^2 - 1}{h}}{2} = \dfrac{\dfrac{2}{h}}{2} = \dfrac{1}{h}.\)
Needless to say, the original post will not work because \(\displaystyle 5 \ne 1.\)